PENGOLAHAN LIMBAH DOMESTIK RUMAH MAKAN DENGAN MOVING BED BIOFILM REACTOR (MBBR) - Aditya Titian Dickdoyo; Okik Hendriyanto Cahyonugroho (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Currently, the number of restaurant businesses is increasing. Wastewater caused by these restaurant activities will be a problem for the environment. Processing of restaurant wastewater can be done by biological treatment because it can reduce the organic content in wastewater. The biological processing process that can be used is the Moving Bed Biofilm Reactor (MBBR) system. The MBBR process in principle is biological growth using suspended and embedded cultures which are mixed in a reactor with aeration and moving media. This study aims to determine the performance of MBBR in reducing BOD, TOC and TSS in restaurant wastewater. The media used were Kaldness K3 and Bioball with various media compositions, namely 100% K3 Kaldness, 100% Bioball, 50% K3 Kaldness and 50% Bioball, 60% K3 Kaldness and 40% Bioball, 40% K3 Kaldness and 60% Bioball. The second variation is the sampling time, namely 3 hours, 6 hours, 9 hours, 12 hours, and 15 hours. Based on the results of this study indicate that the optimum MBBR reactor capability is with a composition of 100% K3 Kaldness at a sampling time of 15 hours. The reactor can reduce TOC by 97.84% and for the decrease in TSS by 76.84%.